Золотая книга лучших сказок мира - Шалаева Галина Петровна (АСТ, 1999)
Экземпляры: аб. (1999) / Инвентарный номер: 41477 / Цена: / Сис.шифр: 82.3(0)-6 / Авт.знак: З-80 / ГРНТИ: 17.82.93 / ББК: 82.3(0)-6